The legend of Ochi [videorecording (Blu-Ray)] - Saxon, Isaiah; Zengel, Helena, 2008-; Wolfhard, Finn, 2002-; Watson, Emily, 1967-; Dafoe, Willem; Longstreth, Dave; Prosofsky, Evan; Warn, Elizabeth (A24, 2025)
In a remote village on the island of Carpathia, a shy farm girl named Yuri is raised to fear an elusive animal species known as ochi. But when Yuri discovers a wounded baby ochi has been left behind, she escapes on a quest to bring him home.